The Pursuit of Ruins : Archaeology, History, and the Making of Modern Mexico - Bueno, Christina, 1966- (Book collections on Project MUSE., 2016)
"This book, then, is essentially about objects. It examines how the ruins of the ancient Indians--monuments overtaken by nature and used by foreigners and local people for centuries--were transformed into museum pieces and official sites. It looks at the making of patrimony, how the pots and statues of the Toltecs, Aztecs, and many other ancient cultures became Mexican objects. It does not pretend to be an intellectual or institutional history of archaeology, nor a comprehensive history of the science. Instead, it focuses on archaeology's role in nation building during one of Mexico's pivotal regimes, a dictatorship that is often thought to have brought the country its first modern state. It explores the process of constructing an ancient patrimony and past--the Porfirian government's effort to cast a net over the pre-Hispanic remains and draw them into the fold of the state"--Introduction.